A comparison of complementary and alternative medicine use by gynecology and gynecologic oncology patients. Issue 3 (1st May 2001) - Von Gruenigen, V. E.; White, L. J.; Kirven, M. S.; Showalter, A. L.; Hopkins, M. P.; Jenison, E. L.
Abstract : Our objective was to describe and compare the use of complementary and alternative medicine (CAM) in gynecology and gynecological oncology patients. Five hundred and twenty-nine gynecology and gynecological oncology patients completed a questionnaire regarding CAM use. Overall, 56.3% of gynecology and gynecological oncology patients reported current use of CAM. Therapies used included nutritional supplements (20%), prayer as medical therapy (17%), exercise as medical therapy (12%), megavitamins (10%), and green tea (10%). While 69.5% believed CAM to be beneficial, only 31.6% discussed these therapies with their physician. The women spent a mean of $656.22 on CAM (range $0–$7, 000), with 31.7% receiving some insurance reimbursement. Gynecologic oncology patients ( n =161) used CAM significantly more than gynecology patients ( n =368) (66% vs. 52%, 95% CI=0.046–0.230, P =0.004). Gynecological oncology patients also spent more for CAM, with a mean expenditure of $711 versus $622 by gynecology patients. Within the gynecological oncology patient group, there were 69 patients currently receiving modern medical treatments for cancer; among these patients, 58% reported using CAM; of these, 39.3% communicated their use of CAM to their physician. Patients in this group spent an average of $1, 178 on CAM during their illness, with only 6.3% receiving insurance reimbursement. Benefits from CAM were perceived by 54.5% in this group. We concluded that cancer patients have a higher usage rate and expenditure for CAM, particularly while they are receiving medical therapy, and are more likely to discuss the use of alternative therapies with their physicians. CAM was perceived as helpful by patients despite the lack of scientific data about its effect.